2015
DOI: 10.1016/j.surfcoat.2014.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the initial particle size distribution on the properties of suspension plasma sprayed Al2O3–TiO2 coatings

Abstract: Elsevier Science SA Vicent, M.; Bannier, E.; Carpio, P.; Rayón Encinas, E.; Benavente Martínez, R.; Salvador Moya, MD.; Sánchez, E. (2015). Effect of the initial particle size distribution on the properties of suspension plasma sprayed Al2O3-TiO2 coatings. Surface and Coatings Technology. 268:209-215. AbstractAl 2 O 3 -TiO 2 coatings have been deposited by atmospheric plasma spraying from agglomerated nanostructured powders showing better properties than their conventional (microstructured) counterparts. These… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 37 publications
1
15
0
1
Order By: Relevance
“…Therefore, the great challenge of this first part of the research addresses the preparation and stabilisation of multicomponent aqueous suspensions of submicronic particles of Y-TZP/Al2O3/SiC (referred as SAZ). The literature on the preparation and stabilisation of each of these oxides or their combinations is abundant [22,[24][25][26][27]. There is also previous research on the preparation of highly concentrated, aqueous suspensions of SiC submicronic particles [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the great challenge of this first part of the research addresses the preparation and stabilisation of multicomponent aqueous suspensions of submicronic particles of Y-TZP/Al2O3/SiC (referred as SAZ). The literature on the preparation and stabilisation of each of these oxides or their combinations is abundant [22,[24][25][26][27]. There is also previous research on the preparation of highly concentrated, aqueous suspensions of SiC submicronic particles [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…However, Vicent et al demonstrated that power requirements become lower when solid loading is increased in the case of water suspension, in opposition to what occurs in ethanol suspensions [11]. Therefore, high solid loading suspension deposition is convenient in terms of energy and efficiency, so that thicker coatings can develop with less spraying passes.…”
Section: Introductionmentioning
confidence: 99%
“…The microstructures of SPS ceramics therefore frequently exhibit peculiar features, such as the co-existence of flattened lamellae together with regions made up of sintered, unmelted particles [54,56,57]. The porosity of these coatings also differs considerably from that of conventional atmospheric plasma sprayed ones.…”
Section: Introductionmentioning
confidence: 99%